Analyzing the Efficiency of County Road Provision - Evidence from Eastern German Counties - Carolin Fritzsche (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
This study analyzes the efficiency of the road provision of the local governments of eastern German counties using data envelopment analysis. The provision of roads is a costly public service, which makes an efficiency analysis in this field an interesting subject. I enhance the previous literature by first, examining the differences in the efficiency of eastern German counties; I consider the age of the foundations of roads, which previous studies have not considered due to data limitations. Second, I use a unique dataset on road quality for my efficiency analysis and show that efficiency levels differ from studies that apply proxies, such as the number of accidents, to analyze the quality of roads. These findings indicate there is a great need to develop suitable proxy variables to describe government services. Additional, I show that the correlations between efficiency levels and county characteristics vary greatly depending on the quality indicator used.
Keywords: H41; H72; R51; 330; DEA; technical efficiency; public services; roads.